Guillain Barré Syndrome in a three year old child under treatment for atypical febrile seizure: A case report - Basnet, Rydam; Subedi, Kiran; Bhandari, Bikash; Gongal, Sonsy (Journal of Kathmandu Medical College, 2017)
Guillain-Barré syndrome is the most common cause of acute fl accid paralysis in healthy infants and children. It has an annual incidence of 0.6 to 2.4 cases per 100,000 population and occurs at all ages and in both sexes. The incidence is lower in children ranging from 0.38 to 0.91 cases per 100,000 in the studies and most of these cases ranging from four years to 18 years of age. Hence, the true incidence is even lesser in child younger than four years. We report a case of an early presentation of Guillain-Barré syndrome in child who was also a case of atypical febrile seizure under sodium valproate. Keeping in mind all the possibilities of acute onset weakness including orthopedic problems, possible side effect of valproate and possible new seizure, treatment was started early solely based on history and physical examination later confirmed by laboratory investigations. Journal of Kathmandu Medical College Vol. 6, No. 1, 2017, page: 35-37